SCREENED—APPROVED / ОЭКРАНЕН ― УТВЕРЖДЕН - Druzhkin Y.C. / ДРУЖКИН Ю.C. (Наука телевидения, 2017)
The author examines the problem of human self-determination, the logical procedure, which is important in everyday life. Human involvement in socio-cultural action affects his perceptions of himself, his understanding of who he is and what community he belongs to. He must go through the processes of maturation and demonstrations. All of this is reflected in the history of cultural movements related to bard (art) song, and with the appearance of man on TV.